Evaluating the impact of Bt rice straw return on Eisenia fetida: AHP analysis, biomarkers, and Bt protein fate - Chuanjun Shi; Junfei Li; Huiru Zhan; Yuanjiao Feng; Jianwu Wang; Zhengao Xiao; Yinghua Shu (Ecotoxicology and Environmental Safety)
A 90-d laboratory experiment was carried out using Bacillus thuringiensis (Bt) rice straws (BTTY and GK775) and non-Bt rice straws (MXZ2, HH1179, and HH38). The objective was to investigate the differences in the effects of Bt and non-Bt rice straws on the earthworm Eisenia fetida. The analytic hierarchy process was applied to assess the risk of returning rice straw to soil on E. fetida by measuring their survival rate, relative growth rate, reproduction, total protein, superoxide dismutase, and glutathione peroxidase (GSH-PX). The results showed that returning Bt rice straw to soil poses no risk to E. fetida over time and that the impacts varied depending on the rice variety. The correlation analysis indicated that GSH-PX activity can be regarded as a biomarker to evaluate the impact of returning rice straw to soil on E. fetida, with GSH-PX activity negatively correlated with potential risk. Cry1Ab protein degraded rapidly, with E. fetida activity slightly accelerating the process. The rice variety was a key factor affecting soil nutrients among the different rice straw treatments, which significantly affected E. fetida’s biological and biochemical parameters. Therefore, returning rice straw to soil presented different effects on E. fetida owing to the differences in rice variety rather than the presence of Cry1Ab protein.